2006
DOI: 10.1096/fj.05-4715fje
|View full text |Cite
|
Sign up to set email alerts
|

Polysurgery of cell sheet grafts overcomes diffusion limits to produce thick, vascularized myocardial tissues

Abstract: Recently, the field of tissue engineering has progressed rapidly, but poor vascularization remains a major obstacle in bioengineering cell-dense tissues, limiting the viable size of constructs due to hypoxia, nutrient insufficiency, and waste accumulation. Therefore, new technologies for fabricating functional tissues with a well-organized vasculature are required. In the present study, neonatal rat cardiomyocytes were harvested as intact sheets from temperature-responsive culture dishes and stacked into cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
347
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 459 publications
(357 citation statements)
references
References 35 publications
5
347
2
3
Order By: Relevance
“…Nevertheless, one disadvantage of this approach is that it is difficult to construct thick tissues as each layer is around 30 lm thick. Multisurgeries such as 10 layers to form a 300 lm thick myocardial patch are required [104,105]. This is less clinically feasible as multiple surgeries in patients are unlikely and therefore preformed patches are needed.…”
Section: Scaffolding Approaches In Tissue Engineeringmentioning
confidence: 99%
“…Nevertheless, one disadvantage of this approach is that it is difficult to construct thick tissues as each layer is around 30 lm thick. Multisurgeries such as 10 layers to form a 300 lm thick myocardial patch are required [104,105]. This is less clinically feasible as multiple surgeries in patients are unlikely and therefore preformed patches are needed.…”
Section: Scaffolding Approaches In Tissue Engineeringmentioning
confidence: 99%
“…So far, using temperature-responsive culture surfaces, we have established numerous types of carrier-free cell sheets derived from epidermal keratinocytes [18], renal epithelial cells [26,27], periodontal ligaments [28,29], retinal pigment epithelium [30], Thyroid cells [31], periosteal cells [32], cardiomyocytes [33,34] and oral mucosal epithelial cells [35,36]. In addition, we demonstrated that multilayered cell sheets enable the construction of 3-dimensional tissues with much higher cell density compared to the traditional way using biodegradable scaffolds [37][38][39].…”
Section: Cell Sheet Engineering Based On Temperatureresponsive Culturmentioning
confidence: 99%
“…Pre-vascularized skeletal muscle constructs from cultures of myoblasts, implantation in vivo of muscle constructs, engineered skeletal muscle constructs, and fibrin gel being placed around a preformed ectopic arteriovenous are all techniques that have been tested and proven as successful in rats [88], making it apparent that the previously mentioned cell sheet practice over scaffolds holds a large amount of potential in relation to the concerted vascularization of muscle constructs. It was found that if neovascularization does, in fact, result from this process, new cell sheets can be applied in layers after neovascularization has already occurred on the previous layers of cell sheets [89]. After this, the required thick muscle tissue with vessels that are able to connect is formed.…”
Section: Vascularizationmentioning
confidence: 99%
“…After this, the required thick muscle tissue with vessels that are able to connect is formed. Although this process has not been used to create skeletal muscle, the aforementioned combination of techniques together with a layer-by-layer polysurgery technique and a fibrin coating would make its creation possible for human use in the development of skeletal/facial tissue [89].…”
Section: Vascularizationmentioning
confidence: 99%